TEMBILAHAN COMMUNITY'S UNDERSTANDING OF PEER TO PEER LENDING SERVICES: A QUALITATIVE STUDY - Anjeli Dhira Elfira; Andi Mansur (MANKEU (JURNAL MANAJEMEN KEUANGAN), 2025)
The development of digital technology has encouraged the birth of various innovations in the financial sector, one of which is financial technology (fintech) services in the form of peer to peer lending (P2P lending). The presence of P2P lending is expected to be able to increase financial inclusion by providing quick and easy access to financing for the public. However, the rapid development of this service is not always accompanied by an adequate level of public understanding. This research aims to explore and understand in depth the understanding, perception, and factors that affect the people of Tembilahan towards P2P lending services. This study uses a qualitative approach with a qualitative descriptive method. Data collection was carried out through in-depth interviews, observations, and documentation of the selected Tembilahan community using purposive sampling techniques. Data analysis is carried out through the stages of data reduction, data presentation, and conclusion drawing by applying triangulation of sources and techniques to maintain the validity of the data. The results of the study show that the level of understanding of the Tembilahan community towards P2P lending is still relatively low. People generally only understand P2P lending as an online loan without understanding the mechanism, legality, and risks that come with it. Public perception of P2P lending is ambivalent, namely on the one hand it is seen as a quick solution to fund needs, but on the other hand it is considered risky due to high interest rates, aggressive collection, and misuse of personal data. Digital financial literacy and information sources, especially social media, are the main factors that affect public understanding and perception. This low understanding has an impact on people's attitudes that tend to avoid P2P lending altogether or use it without careful consideration.